A phase 2 study of inotuzumab ozogamicin in patients with indolent B‐cell non‐Hodgkin lymphoma refractory to rituximab alone, rituximab and chemotherapy, or radioimmunotherapy. (22nd April 2016) - Goy, Andre; Forero, Andres; Wagner‐Johnston, Nina; Christopher Ehmann, W.; Tsai, Michaela; Hatake, Kiyohiko; Ananthakrishnan, Revathi; Volkert, Angela; Vandendries, Erik; Ogura, Michinori
Abstract : This phase 2 study evaluated the efficacy and safety of inotuzumab ozogamicin (InO) in patients with indolent B‐cell non‐Hodgkin lymphoma (NHL) refractory to rituximab alone, rituximab plus chemotherapy or anti‐CD20 radioimmunotherapy. Patients received InO 1·8 mg/m 2 intravenously on a 28‐d cycle for a planned 4–8 cycles. The initial InO dose and schedule could be adjusted for tolerability and patients were allowed to receive 2 additional cycles (up to 8 total) after achieving a complete response (CR). The primary endpoint was overall response. Eighty‐one patients were enrolled, among whom 48 (59%) received ≥3 InO cycles and 13 (16%) completed the treatment phase. The overall response rate was 67% (CR, 31%). Median (95% confidence interval) progression‐free survival was 12·7 (8·9–26·9) months; median overall survival was not reached. Haematological adverse events (AEs) were common, particularly thrombocytopenia (74%) and neutropenia (56%). These were also the most common AEs leading to treatment discontinuation (37% and 11%, respectively); 58% of patients reported AEs leading to treatment discontinuation. InO demonstrated robust activity in these heavily pretreated patients, although treatment duration was limited by haematological toxicities. Additional studies may determine dosing regimens that allow for reduced toxicity.